Global supply chain quality management : product recalls and their impact - Flynn, Barbara B.; Zhao, Xiande (Boca Raton, FL : CRC Press, 2015)
While there is substantial research surrounding manufacturing and design-related product hazards, little has been written about supply chain product hazards and how they impact supply chain quality management. Filling this need, Global Supply Chain Quality Management: Product Recalls and Their Impact draws together key insights and research findings from a global research project on product safety and recalls. The book presents detailed case studies of six extended global supply chains within three industries: toys, food, and pharmaceuticals. These case studies cover U.S. companies with supply chains that extend into China and provide the perspectives of both U.S. and Chinese executives. It includes coverage of several highly publicized product recalls, including Ford Pinto, Extra Strength Tylenol, melamine-tainted milk, Mattel, and Toyota. Presenting detailed examples of both poor and best practices, the text supplies firsthand accounts from key players in well-known product recalls. It outlines an event study methodology that can help readers determine the true financial impact of a product recall announcement. It also describes how to conduct controlled experiments to determine the effect of various recall strategies on consumers. The book describes how alternative product recall strategies can influence consumers' perceptions of your organization's corporate social legitimacy as well as their future purchasing behaviors. Although the text focuses on product quality within the supply chain, it also sheds light on other sources of product hazards-sharing wide-ranging perspectives and current methodologies. Book jacket.
Includes bibliographical references and index.
Keywords: Product recall; Product safety; Business logistics; Materials management; Quality control